A Union Woman in Civil War Kentucky : The Diary of Frances Peter - Peter, Frances Dallam, 1843-1864 (Book collections on Project MUSE., 2000)
Frances Peter was one of the eleven children of Dr. Robert Peter, a surgeon for the Union army. The Peter family lived on Gratz Park near downtown Lexington, where nineteen-year-old Frances began recording her impressions of the Civil War. Because of illness, she did not often venture outside her home but was able to gather a remarkable amount of information from friends, neighbors, and newspapers. Peter's candid diary chronicles Kentucky's invasion by Confederates under Gen. Braxton Bragg in 1862, Lexington's month-long occupation by Gen. Edmund Kirby Smith, and changes in attitude among the.